Unknown, forgotten and (re)discovered: a possible new life for three fortresses near the town of Kavarna (Research Announcements "Heritage BG", 2025)
The paper represents the results of ethnographical research focused on the policies of local authorities and attitudes of media and communities on topics related to protection and promotion of immovable heritage of local importance in Kavarna Municipality. Three case studies, concerning the remains of fortified settlements reveal the different approaches towards cultural heritage that is left aside of venues of high national interest and the potential of these little-known sites to gain recognition. Methodological approach included documentary and media analyses and ethnographic fieldwork. References:Primary sources:Cultural Heritage Act 2009: Cultural Heritage Act 2009. Available at: https://lex.bg/laws/ldoc/2135623662 (13.01.2023)IDPM Balchik 2021: Project for Integrated Development Plan of the Municipality of Balchik 2021. Available at: https://balchik.bg/files/info_pages/PIRO_Balchik_2021-2027_final_za_publikuvane.pdf (07.05.2023)IEFEM –AEIM 1236-III 2022: Ivanova, Vanya. Field Materials on Topic: ‘Local Policies in the Field of Conservation of Immovable Cultural Property of Local Importance in Municipalities Sandanski, Balchik, Kavarna and Garmen’. Scientific Information and Documentation Archive at IEFEM – BAS.IEFEM – AEIM 1240-III 2022: Popcheva, Julia. Field Materials on Topic ‘Importance of ICH with LI for Local Communities and Media Involvement in their Promotion’. Scientific Information and Documentation Archive at IEFEM – BAS.IEFEM – AEIM 1241-III 2022: Erolova, Yelis. Field Materials on Topic: ‘Management of Immovable Cultural Heritage with Local Importance in Balchik Municipality and Kavarna Municipality’. Scientific Information and Documentation Archive at IEFEM – BAS.PIDPM Kavarna 2021: Project for Integrated Development Plan of the Municipality of Kavarna 2021. Available at: https://www.kavarna.bg/umbraco/surface/DownloadService/kavarna9f8d.pdf?id=40377 (09.05.2023)Secondary sources:Asenova et al. 2021: Asenova, Mariana, Vasil Marinov, Vera Nikolova, Elena Petkova, Radenka Mitova, Chayana Istatkova. Between Culture and Tourism: Tourist Attractions Based on Cultural Heritage. Sofia.Bobcheva 1974: Bobcheva, Lyubka. Archeological Map of Tolbuhin District. Sofia.Bobcheva 1982: Bobcheva, Lyubka. Early Medieval Bulgarian Settlements and Necropoleis on the South-Dobrudjan Black Sea Coast. In: Medieval Bulgaria and Black Sea Coast (ed. Aleksandar Kuzev). Varna, 99 – 108.Dimitrova 2007: Dimitrova, Yana. About the Thracian Presence at Kaliakra Fortress and Its Surroundings. In: Kavarna – the Centre of the Bulgarian North-east (eds. Boni Petrunova, Hristo Kuzov, Darina Mircheva). Veliko Tarnovo, 25 – 41.Kavarna.bg: Offical website of Kavarna Municipality. Culture and Tourism. Festivals. Available at: http://www.kavarna.bg/kultura-i-turizym/124-festivali (09.02.2023)Kuzov, Manolova-Voykova, Rocov 2007: Kuzov, Hristo, Maria Manolova-Vojkova, Teodor Rokov. Timum – A Not Well-known Town of Dobrudja Coast. In: Kavarna – the Centre of the Bulgarian North-east (eds. Boni Petrunova, Hristo Kuzov, Darina Mircheva). Veliko Tarnovo, 140 – 150.Petrunova 2008: Petrunova, Boni. Tourist Sites in Kavarna Municipality – Fakel, 31(1644), 3.Petrunova 2008a: Petrunova, Boni. Tourist Sites in Kavarna Municipality – Fakel, 32(1645), 3.Petrunova 2012: Petrunova, Boni. The wealth of Kaliakra. Discoveries. Findings. Hypotheses. Varna.Rusalkaresort: Official website of Rusalka Resort. Available at: https://rusalkaresort.com/ (23.03.2023)Torbatov 2002: Torbatov, Sergej. The Defense System of the Late Roman Province of Scythia: The end of the 3rd – the 7th century AD. Veliko Tarnovo.TravelNews 2021: Kavarna Municipality Is a Finalist for Prestigious Black Sea Awards 19.07.2021. Available at: https://www.travelnews.bg/bg/news/16266913808307/obshtina-kavarna-e-finalist-za-prestizhni-chernomorski-nagradi (20.03.2023)Velev, Vasilev 1982: Velev, Mitrofan, Vasil Vasilev. Chirakman-Karvuna-Kavarna. Sofia.Vladimirov 2021: Vladimirov, Zhelyu. Cultural Heritage as a Resource for Local Development Research Announcements. Bulletin ‘Heritage BG’, ed. Emmanuel Moutafov, N1, 2021, 9 –15.
Keywords: immovable cultural heritage; local importance; fortified settlements; heritage promotion